1994
DOI: 10.1002/mcs.1220060507
|View full text |Cite
|
Sign up to set email alerts
|

Functional group selectivity using fluoroform as a mobile phase for supercritical fluid chromatography

Abstract: Abstract. The eluotropic strength and chromatographic selectivity of fluoroform is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 6 publications
1
8
0
Order By: Relevance
“…Additional evidence of hydrogen bonding has been reported by Blackwell and Schallinger (1994), as naphthalene with a hydroxyl group substituted in the 1-position exhibited a 50% decrease in the capacity factor (kЈ) with trifluoromethane compared to pure carbon dioxide. They attributed this observation to the ability of trifluoromethane to interact with the analyte via hydrogen bonding interaction, and concluded that other types of dipole interactions were less important, and that functional groups capable of interacting with trifluoromethane through hydrogen bonding were affected chomatographically to a greater extent than those which were polarizable, but unable to hydrogen bond.…”
Section: Alternate Fluids For Enhancing Extraction Selectivitysupporting
confidence: 59%
“…Additional evidence of hydrogen bonding has been reported by Blackwell and Schallinger (1994), as naphthalene with a hydroxyl group substituted in the 1-position exhibited a 50% decrease in the capacity factor (kЈ) with trifluoromethane compared to pure carbon dioxide. They attributed this observation to the ability of trifluoromethane to interact with the analyte via hydrogen bonding interaction, and concluded that other types of dipole interactions were less important, and that functional groups capable of interacting with trifluoromethane through hydrogen bonding were affected chomatographically to a greater extent than those which were polarizable, but unable to hydrogen bond.…”
Section: Alternate Fluids For Enhancing Extraction Selectivitysupporting
confidence: 59%
“…Blackwell and Schallinger investigated the eluotropic strength and selectivity of fluoroform compared to CO 2 and CO 2 /methanol for the analysis of naphthalene derivatives. They found that fluoroform is much stronger than the other mobile phases at the same temperature and pressure but is weaker under the same reduced conditions (60). These authors also investigated hydrofluorocarbon and perfluorocarbon mobile phases.…”
Section: Supercritical Fluid Chromatographymentioning
confidence: 97%
“…[ [20][21][22]. Chimowitz, et al, have modeled this retention behavior in terms of the difference between the ideal heat of solution of the analyte in the mobile phase and the analyte heat of adsorption on the stationary phase using the following equation [15][16][17]:…”
Section: General Retention Behaviormentioning
confidence: 99%